Reprint of "Quality management, environmental management maturity, green supply chain practices and green performance of Brazilian companies with ISO 14001 certification: Direct and indirect effects". (February 2015) - Jabbour, Ana Beatriz Lopes de Sousa; Jabbour, Charbel Jose Chiappetta; Latan, Hengky; Teixeira, Adriano Alves; de Oliveira, Jorge Henrique Caldeira
Highlights: This study aims to test a new conceptual model based on the Brazilian reality. This study discusses concepts of sustainable operations management. Improvement in firms' green performance will require a systemic approach. External GSCM practices influence firms' green performance. The public sector should pay special attention to smaller companies. Abstract: This study aims to test a new conceptual model based on the relationship between quality management (QM), environmental management maturity (EMM), adoption of external practices of green supply chain management (GSCM) (green purchasing and collaboration with customers) and green performance (GP) with data from 95 Brazilian firms with ISO 14001. To our knowledge, such links and relationships are not simultaneously identified and tested in the literature. The results indicate the validation of all of the research hypotheses. This paper highlights that an improvement in green performance will require attention to quality management, environmental management maturity, and green supply chain.